2018
DOI: 10.3847/1538-4357/aaa3f8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of GeV Gamma-Ray Emission in the Direction of HESS J1731-347 with Fermi-LAT

Abstract: We report the detection of GeV γ-ray emission from supernova remnant HESS J1731-347 using 9 years of Fermi Large Area Telescope data. We find a slightly extended GeV source in the direction of HESS J1731-347. The spectrum above 1 GeV can be fitted by a power-law with an index of Γ = 1.77 ± 0.14, and the GeV spectrum connects smoothly with the TeV spectrum of HESS J1731-347. Either a hadronic-leptonic or a pure leptonic model can fit the multi-wavelength spectral energy distribution of the source. However, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…data performed by Abramowski et al (2011) showed a shell structure in the TeV band and a powerlaw spectrum with a high-energy cutoff. In the GeV band, no emission was found in early studies (Yang et al 2014;Acero et al 2015), but a point source with hard spectrum toward this remnant was detected by Fermi-LAT with more accumulated data (Condon et al 2017;Guo et al 2018). These observational features are very similar to the young SNR RX J1713.7−3946, but their ages are quiet different.…”
Section: Rcw 86 (G3154−23)mentioning
confidence: 84%
“…data performed by Abramowski et al (2011) showed a shell structure in the TeV band and a powerlaw spectrum with a high-energy cutoff. In the GeV band, no emission was found in early studies (Yang et al 2014;Acero et al 2015), but a point source with hard spectrum toward this remnant was detected by Fermi-LAT with more accumulated data (Condon et al 2017;Guo et al 2018). These observational features are very similar to the young SNR RX J1713.7−3946, but their ages are quiet different.…”
Section: Rcw 86 (G3154−23)mentioning
confidence: 84%
“…In addition, we found that the GeV spectrum is harder than previous work. Such a hard spectrum is similar to SNR RCW 86 [17], RX J0852.0-4622 [18] and HESS J1731-347 [19]. Future more multi-wavelength observations will be helpful to explore the radiation mechanism.…”
Section: Pos(icrc2021)629mentioning
confidence: 67%
“…We compare HESS J1640-465 with other SNRs which have the similar γ-ray spectra with HESS J1640-465 (Funk 2015;Guo et al 2017a), such as RX J1713-3946 (Abdo et al 2011;Yuan et al 2011;Zeng et al 2017), RX J0852-4622 (Tanaka et al 2011), RCW 86 (Yuan et al 2014, SN1006 (Acero et al 2010;Araya & Frutos 2012;Xing et al 2016;Condon et al 2017), and HESS J1731-347 (H.E.S.S. Collaboration et al 2011;Guo et al 2018;Condon et al 2017). These SNRs are dynamically younger with fast efficient shocks.…”
Section: Discussionmentioning
confidence: 90%
“…While for dynamically younger SNRs with fast efficient shocks, such as RX J1713-3946 (Yuan et al 2011;Zeng et al 2017; H. E. S. S. Collaboration et al 2016a), RCW 86 (Yuan et al 2014;Ajello et al 2016), and HESS J1731-347 (H.E.S.S. Collaboration et al 2011;Guo et al 2018;Condon et al 2017), the γ-ray emission is usually thought to be from the leptonic process. For PWNe, however, the γ-ray emission is mostly contributed by the leptonic process, such as Vela X (Abdo et al 2010a;Aharonian et al 2006a; H. E. S. S. Collaboration et al 2012), MSH 15-52 (Abdo et al 2010b;Aharonian et al 2005), and HESS J1825-137 (Aharonian et al 2006b;Grondin et al 2011).…”
Section: Introductionmentioning
confidence: 99%